High-Performance Field-Effect Transistors and Phototransistors Array Based on Solution-Processed Quasi-1D Van der Waals Ta2Pd3S8 Crystals - Choi, Kyung Hwan; Lee, Bom; Kang, Jinsu; Jeong, Byung Joo; Cho, Sooheon; Lee, Sang Hoon; Kim, Dahoon; Kim, Yeong Hyeop; Chang, Jongwha; Oh, Hyung Suk; Kim, Ji Hee; Lee, Jae Hyun; et al. (Advanced Functional Materials, 2025)
Quasi-1D van der Waals (vdW) materials, particularly the M2N3X8 family, have emerged as promising candidates for nanoelectronic platforms due to their excellent carrier transport properties and structural diversity. Among these, Ta2Pd3S8, a theoretically proposed member, has remained unexplored. In this study, Ta2Pd3S8 is successfully synthesized for the first time and optimize its exfoliation into nanowires through liquid phase exfoliation, achieving scalable production using a liquid cascade centrifugation technique. Two types of field-effect transistors (FET) devices are fabricated: single nanowire devices and network structure arrays. The single nanowire FETs demonstrate high field-effect mobility of up to 27.3 cm2 V−1 s−1 with an Ion/Ioff of 4.31 × 104, while the network devices exhibit uniform performance across 5 × 5 arrays. Furthermore, optoelectronic characterization reveals excellent photodetection capabilities, including a responsivity of 322.40 A W−1 for single nanowire devices and 1.85 mA W−1 for network structures. These results highlight the potential of Ta2Pd3S8 as a versatile material for low-dimensional electronic and optoelectronic applications, paving the way for its integration into next-generation multifunctional devices.
Keywords: 1D van der Waals; field-effect transistors; large-area devices; liquid phase exfoliation; nanowires; phototransistors; solution-processing